2020
DOI: 10.1002/arch.21729
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromones and olfactory proteins in Antheraea moths: A. pernyi and A. polyphemus (Lepidoptera: Saturniidae)

Abstract: Olfaction is essential for regulating the physiological and behavioral actions of insects with specific recognition of various odors. Antheraea moths (Lepidoptera: Saturniidae) possess relatively large bodies and antennae so that they are good subjects for exploring molecular aspects of insect olfaction. Current knowledge of the molecular aspects of Antheraea olfaction is focused on the Chinese tussah silkmoth A. pernyi Guérin‐Méneville and another species A. polyphemus (Cramer) in their pheromones, odorant‐bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Based on homology with CD36, DmelSnmp2 might serve as transporters and receptors for lipids and lipid‐protein complexes and contribute to removing lipophilic odors in sensory lymph (Strotmann & Breer, 2011). Li et al (2020) suggested that SNMPs are likely to contribute to sex‐pheromone detection, inactivation, and degradation together with ODEs. However, the recent study revealed that the ortholog of DmelSNMP2 is BmorSNMP3 , which was expressed in larval midguts and may be involved in the immunity response to the virus and bacterial infections (Xu et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Based on homology with CD36, DmelSnmp2 might serve as transporters and receptors for lipids and lipid‐protein complexes and contribute to removing lipophilic odors in sensory lymph (Strotmann & Breer, 2011). Li et al (2020) suggested that SNMPs are likely to contribute to sex‐pheromone detection, inactivation, and degradation together with ODEs. However, the recent study revealed that the ortholog of DmelSNMP2 is BmorSNMP3 , which was expressed in larval midguts and may be involved in the immunity response to the virus and bacterial infections (Xu et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For instance, within hymenopterans, the number of orthologues ranges from six (Yang et al, 2017 ) to 54 (Nie et al, 2018a , 2018b ) and these OBP orthologues differ in how specifically they bind certain ligands; with pheromone binding OBPs typically being highly specific and OBPs binding environmental odours having multiple ligands (reviewed in Venthur & Zhou, 2018 ). Through this variation in specificity, OBPs influence how strongly a SN and thus, an individual, responds to different cues (Godoy et al, 2021 ; Li, Wang, & Zhang, 2020 ).…”
Section: Mechanism 2: Odourant Binding Proteinsmentioning
confidence: 99%
“…Antheraea pernyi (Guérin-Méneville, Lepidoptera: Saturniidae) is not only an important economic insect for silk production but also a rising Lepidoptera model organism with several advantages, such as the ease of rearing and experimental operation (Li et al 2016), and the adult moths have relatively large bodies and antennae, so that they are good subjects for exploring molecular aspects of insect olfaction. Although several PBPs have been identified in A. pernyi (Li et al 2020), there is still a lack of detailed reports on response mechanisms of male moths to female stimulation especially the related proteins and metabolites underlying the female pheromone signal transmission in the male antennae of A. pernyi . It has been investigated the mechanisms of multiple physiological and pathological processes in A. pernyi (Li et al 2016, Wang et al 2019a, 2019b) by HTS technologies.…”
Section: Introductionmentioning
confidence: 99%